Impaired Cell Viability and Functionality of Hepatocytes After Incubation With Septic Plasma—Results of a Second Prospective Biosensor Study - Sauer, Martin; Haubner, Cristof; Richter, Georg; Ehler, Johannes; Mencke, Thomas; Mitzner, Steffen; Margraf, Stefan; Altrichter, Jens; Doß, Sandra; Nöldge-Schomburg, Gabriele (Frontiers in Immunology, 2018)
Liver dysfunction (LD) and liver failure are associated with poor outcome in critically ill patients. In patients with severe sepsis or septic shock, LD occurred in nearly 19% of patients. An early diagnosis of LD at time of initial damage of the liver can lead to a better prognosis of these patients because an early start of therapy is possible. We performed a second prospective study with septic patients to test a new cell-based cytotoxicity device (biosensor) to evaluate clinical relevance for early diagnosis of LD and prognostic capacity. In the clinical study, 99 intensive care unit patients were included in two groups. From the patients of the septic group (n = 51, SG), and the control (non-septic) group [n = 49, control group (CG)] were drawn 20 ml blood at inclusion, after 3, and 7 days for testing with the biosensor. Patients’ data were recorded for hospital survival, organ function, and demographic data, illness severity [acute physiology and chronic health evaluation (APACHE) II-, sepsis-related organ failure assessment (SOFA) scores], cytokines, circulating-free deoxyribonucleic acid/neutrophil-derived extracellular traps (cf-DNA/NETs), microbiological results, and pre-morbidity. For the developed cytotoxicity test, the human liver cell line HepG2/C3A was used. Patients’ plasma was incubated in a microtiter plate assay with the test cells and after 6 days incubation the viability (trypan blue staining, XTT-test) and functionality (synthesis of albumin, cytochrome 1A2 activity) was analyzed. An impairment of viability and functionality of test cells was only seen in the SG compared with the CG. The plasma of non-survivors in the SG led to a more pronounced impairment of test cells than the plasma of survivors at inclusion. In addition, the levels of cf-DNA/NETs were significantly higher in the SG at inclusion, after 3, and after 7 days compared with the CG. The SG showed an in-hospital mortality of 24% and the values of bilirubin, APACHE II-, and SOFA scores were markedly higher at inclusion than in the CG. Hepatotoxicity of septic plasma was already detected with the liver cell-based biosensor at inclusion and also in the course of disease. The biosensor may be a tool for early diagnosis of LD in septic patients and may have prognostic relevance.